I contain multitudes : the microbes within us and a grander view of life - Yong, Ed, 1964- (Ecco, an imprint of HarperCollinsPublishers, 2016)
This book lets us peer into the world of microbes -- not as germs to be eradicated, but as invaluable parts of our lives -- allowing us to see how ubiquitous and vital microbes are: they sculpt our organs, defend us from disease, break down our food, educate our immune systems, guide our behavior, bombard our genomes with their genes, and grant us incredible abilities. While much of the prevailing discussion around the microbiome has focused on its implications for human health, Yong broadens this focus to the entire animal kingdom, prompting us to look at ourselves and our fellow animals in a new light: less as individuals and more as the interconnected, interdependent multitudes we are. I Contain Multitudes is the story of extraordinary partnerships between the familiar creatures of our world and those we never knew existed. It will change both our view of nature and our sense of where we belong in it. --